Some Inequalities for Power Means; a Problem from "The Logarithmic Mean Revisited". Issue 3 (16th March 2023) - Jameson, G. J. O.
Abstract: We establish some inequalities comparing power means of two numbers with combinations of the arithmetic and geometric means. A conjecture from [1 ] is confirmed.